THE ROLE OF MEDIATING JOB SATISFACTION TO IMPROVE ORGANIZATIONAL JUSTICE AND TURNOVER INTENTIONS - Abdullah Rosyid Wicaksono; Shofia Amin; Agus Solihin (Management Department, Faculty of Economics and Business, Universitas Jambi, 2021)
This study aims to examine the effect of Organizational Justice on Turnover Intention at PT. Tiga Serangkai Pustaka Mandiri in Sumatra regional office, either directly or through Job Satisfaction as a mediating variable. The study used a survey research design by distributing questionnaires to 101 employees. This study measures Organizational Justice as an independent variable, Job Satisfaction as a mediating variable, and Turnover Intention as the dependent variable. The data was analyzed by PLS-SEM with the SmartPLS 3.0 software tool. The results showed that organizational justice has a negative and significant effect on employees' turnover intention, either directly or through Job Satisfaction. In addition, this study found that job satisfaction can explain the impact of organizational justice on the employees’ turnover intentions of PT. Tiga Serangkai Pustaka Mandiri in Sumatra regional office.